The Joint Action of Metal and Enzymatic Nanoparticles Used for Functionalization of Protective Self-Cleaning Materials Neutralizing Organophosphates and Possessing Bactericide Activity - V. V. Zavyalov; N. V. Zavyalova; V. I. Kholstov; V. A. Kovtun; V. K. Gorelenkov; G. A. Frolov; I. V. Lyagin; N. A. Stepanov; A. G. Aslanli; E. N. Efremenko (Вестник войск РХБ защиты, 2023)
The combination of several modules, including metal nanoparticles (tantalum or zinc), antimicrobial substances,  enzyme nanocomplexes that provide self-purification (self-degassing) and multiple functionalization, makes it possible  to create materials that provide protection against chemical and biological damaging agents. The purpose of this work  is to study the combined effect of metal nanoparticles, other biocidal compounds, and nanosized enzyme complexes  of hexidine-containing organophosphate hydrolase and penicillin acylase deposited on unified tissue platforms on  organophosphorus compounds and bactericidal activity. Materials and research methods. The protective self-cleaning  material was created on the basis of the principle of constructing modular materials with desired properties. Nanosized  metal complexes and enzymatic non-covalent polyelectrolyte complexes with polyglutamic acid or antimicrobial  peptides were applied to a tissue unified platform in a certain sequence and in a certain amount, and its antitoxic  and antimicrobial properties were studied. The discussion of the results. With the simultaneous operation of several  modules, subject to certain requirements for applying the quantity and sequence, the properties of the modules are  preserved, which do not neutralize or disable the specific properties of the modules and do not interfere with other  modules to perform their functions. The best results of such materials can be obtained by combining biologically inert  Ta nanoparticles and a stabilized enzyme in a polyelectrolyte complex. To acquire antimicrobial properties, fibrous  materials can be functionalized not only by a combination of metal nanoparticles with enzyme preparations, but  also by a combination of low molecular weight antibiotics with enzymes. Conclusions. The studies performed have  demonstrated the possibility of combining modules containing metal carboxylates, metal nanoparticles, and enzyme  nanocomplexes for multiple functionalization of the same fibrous materials, which acquired biocidal and antichemical  protective properties. New self-degassing materials have been obtained that have protective chemical and biological  properties and high stability in terms of catalytic activity with respect to the main substrates of the introduced enzymes  and bactericidal activity. The use of such approaches makes it possible to impart protective properties to almost any  fabric or clothing made from it, on which the studied modules will be applied, which will provide the required level of  protection for personnel and have a debilitating and chilling effect.